Análise distribuição da carga hidráulica e vazão na unidade operacional de um sistema de irrigação localizada - Marcussi, Francisco F.N.; Saad, João Carlos Cury [UNESP]; de Souza, Saulo A.; Barreto, Carlos E.A.G. (My University, 2007)
The different combination possibilities of emission uniformity and field slope within the operational unities of localized irrigation systems favor the occurence of some configurations in the irrigation system, and consequently different hydraulic head distributions, discharge and system management. After the system has been implanted, it is necessary to verify pressure and discharge distribution in the operational unit. This work objective was to verify pressure and discharge uniformity on derivation line and lateral lines with micro sprinkle in data gotten from operational research. The results allow to check that despite analyzed declivity; the higher the emission uniformity calculated for the line of derivation in the project is, the higher its pressure uniformity is. Previously the results of discharge in the emitters of the operational unit showed a constant variation entering the point of higher discharge and lower discharge, even though differently from the three tested irrigation blades.
Analysis of load hydraulic uniformity and discharge in the operational unit of an irrigation system
Keywords: Hydraulic head; Irrigation; Pressure uniformity; Discharge (fluid mechanics); Hydraulic equipment; Pressure regulation; Water management; discharge; hydraulic head; irrigation system; pressure effect; spatial distribution